ANALYSIS OF FINANCIAL SYSTEM STABILITY IN INDONESIA: A PRINCIPAL COMPONENT ANALYSIS APPROACH - Putra, I Gede Putu Wahyu Brianala Genta; Yasa, I Nyoman Mahaendra (Ridwan Institute, 2025)
This study uses Principal Component Analysis (PCA) to analyze the stability of Indonesia's financial system using 15 indicators from banking financial institutions and financial markets. The PCA technique is applied to each variable included in the components of bank financial institutions or non-bank financial institutions into several main factors that have the same variant value. The first principal component (PC1) successfully captured around 38 percent of the total variability and became the dominant indicator for financial system stability in Indonesia. In addition, from the banking financial institution indicators, NIM and LDR became factors that had quite an influence on PC1, indicating that profitability and banking intermediation activities still played a role in the dynamics of financial system. Furthermore, the interplay between Credit Default Swaps (CDS), exchange rates, and stock market indicators like the IHGS could provide deeper insights into how these elements influence investor sentiment and overall financial stability. Therefore, more comprehensive policy steps are needed to strengthen the resilience of the financial system, including stabilizing the bond market, managing exchange rate risk, and strengthening monetary and macroprudential policies to face future economic uncertainty.